Support for Bidirectional Model-to-Text Transformations - Anjorin, Anthony; Lauder, Marius; Schlereth, Michael; Schürr, Andy (Electronic Communications of the EASST, 2011)
In recent years, model-driven approaches and processes have established themselves as pragmatic and feasible solutions with tangible advantages. Transformations play a central role in any model-driven solution and, as interest in textual modelling grows, providing concepts and tools for supporting a high-level and declarative speciﬁcation of bidirectional model-to-text transformations becomes a vital area of research. Our paper identiﬁes important areas and scenarios for model-to-text transformations that are not or only partially supported by currently existing solutions. Based on the requirements of a real-world case study, we introduce a new concept that has been inspired by a successful bidirectional model-to-model transformation approach: Triple Graph Grammars.